Pengembangan Perekat Likuida dari Limbah Kulit Buah Kakao (Theobroma cacao L.) - Marcelila Medynda; Tito Sucipto; Luthfi Hakim (Program studi Kehutanan USU, 2012)
Increased need for adhesive in the wood processing industry require alternative to meet the needs. Cocoa is one of natural resource that contains lignocelluloses and potential to be alternative adhesive through liquefaction process. This research aim to determine adhesive quality such as visible, degree of acidity (pH), viscosity, density, solid content, gelatin time, ash content , free formaldehyde, and crystalline degree, compare the adhesive quality of cocoa fruit outer skin (CFOS/ KBKL) and inner skin (CFIS/ KBKD), and compare them with SNI 06-4567-1998. Mixed cocoa fruit skin, H2SO4, technical crystal phenol, NaOH and formalin with 90ºC temperature for 2 hours. Result of research showed that cocoa fruit skin adhesive is phenolic group with CFOS was liquid adhesive characteristic, brown colored, waste free, degree of acidity was 10, viscosity was 0,8355 cps, density was 1,156, degree of solid content was 42,33%, gelatin time was 89 minutes 37 seconds, ash content was 9,2%, free formaldehyde was 0,8% and crystalline degree was 35,19% and CFIS characteristic was liquid, reddish brown colored, waste free, degree of acidity was 10, viscosity was 31,202 cps, density was 1,262, degree of solid content was 44,66%, gelatin time was 73 minutes 45 seconds, ash content was 13,8%, free formaldehyde was 0,48% and crystalline degree was 37,28%. CFIS better than CFOS because it has fit with the standards well and also almost standard approach although not according to standard. Cocoa fruit skin liquid adhesive quality were gotten fulfilled SNI 06-4567-1998 enough such as appearance, degree of acidity, degree of solid content and gelatin time. Free formaldehyde characteristic also fulfill of SNI 06-4565-1998 was ≤2% Key word: waste, cocoa fruit outer and inner skin, liquiefaction, wood liquid adhesive